Mapping mangrove distribution in Kong Kong Laut, Masai, Johor, using remote sensing - Ahmadi, Zuhairi; Kassim, Zaleha; Zakariya, Khalilah; Shahari, Rozilawati; Ahmad Mukhlis, Amin; Shammodin, Muhammad Shaheed; Mohd Rosli, Nur Suhaila; Hasnan, Hazwani Hanim; Shammodin, Najehah; Muhammad Idzham Helmi, Mohd Jinah (Malaysian Nature Society, 2020)
This study examined the mangrove distribution in Kong Kong Laut, Masai, Johor using remote sensing. Landsat 8 OLI/TIRS imagery at Kong Kong Laut estuary has been analyzed using NDVI and supervised classification based on the field survey data. In this study, field survey for supervised classification only observed the exclusive mangrove species and does not include the associate species. The total number of exclusive species found is eleven, although there are many other associate mangrove species in the area. Results showed that total cover of 29.63 ha of “Mangrove Class A” consisting of four mangrove species have been identified. Besides, the total cover of “Mangrove Class B” consisting of eleven mangrove species is 9.27 ha. The overlapping mangrove classification is due to the spectral similarities in mangrove vegetation, thus some species cannot be segregated into different groups found in both classes. In addition, the total mangrove cover in Kong Kong Laut is bigger than the classified 38.90 ha as the mentioned figure is only focused on the proposed mangrove conservation area by the local community. It is found that remote sensing is one of the reliable techniques to map the mangrove distribution and coverage, thus allowing continuous monitoring for sustainable planning and management.